Awareness and Perception on the Issues Arising out of Undesirable Pattern of Rainfall of the Rice Farmers - Arunachalam, R.; Sasmitha, R. (Indian Journal of Extension Education, 2020)
Farmers’ awareness and perception on the erratic pattern of rainfall would help to develop appropriate extension educational strategies to manage these issues systematically. The study was conducted in the Madurai district of Tamil Nadu, India with local extension workers, crop scientists and 50 active rice cultivating farmers selected randomly to analyse respondents’ level of awareness and perception. It was reported that high rainfall during nursery stages affects seed germination. Incidences of root rot, chaffy grains formation and soil erosion were also recorded under high rainfall conditions. Leaf mite infestation, mealy bug attack, and bacterial leaf blight disease were more intense during heavy rainfall conditions. Poor rainfall led to, deprived ground water availability, reduction in rice cropped area, intensive weed growth and non-possibility of profitable crop. Erratic rainfall affected growth duration, grain setting, yield and stages of rice crop. At the time of ripening erratic rainfall affected crop growth severely. Based on the findings of the study, a suggestive ‘Climate led Transfer of Technology (ToT)’ Module has been developed.
Keywords: Awareness; Climate change; Documentation; Perception; Rainfall pattern